2013
DOI: 10.1111/nmo.12075
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gastric emptying by radiopaque markers in patients with diabetes: correlation with scintigraphy and upper gastrointestinal symptoms

Abstract: A gastric emptying test with ROM is a widely available screening method to detect delayed gastric emptying in patients with diabetes, where a positive result seems reliable. However, a normal ROM test does not exclude delayed gastric emptying, and if the clinical suspicion of gastroparesis remains, scintigraphy should be performed. Results from scintigraphy also correlate with GI symptom severity, which ROM test did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
2
25
0
1
Order By: Relevance
“…In line with this complex pathophysiology, the association between upper GI symptoms and gastric emptying is modest. Conversely, gastric emptying rate cannot explain the range of upper GI symptoms experienced, neither in DM patients nor in the case of idiopathic gastroparesis [1114]. …”
Section: Introductionmentioning
confidence: 99%
“…In line with this complex pathophysiology, the association between upper GI symptoms and gastric emptying is modest. Conversely, gastric emptying rate cannot explain the range of upper GI symptoms experienced, neither in DM patients nor in the case of idiopathic gastroparesis [1114]. …”
Section: Introductionmentioning
confidence: 99%
“…Ron et al found that early satiety was the only patient-reported symptom associated with delayed gastric emptying, as assessed by breath-test [21]. Prospective studies using validated scoring systems have correlated protean symptoms with gastric retention; however, a wide variability exists [1113, 16]. In fact, delayed gastric emptying rate (GER) is not always associated with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is a non-invasive and quantitative method, but the measurement is rough and disconnected. 3 A magnetic capsule endoscopy may provide continuous visual gastric motility and qualitative aspects of the motility. This report is the first step to develop the novel technique for intra-gastric monitoring of the gastric motility, although there are lots of problems to be solved: the validation should be performed; the quantitative measurement of gastric motility for determining normal motility should be further investigated also; and the cost-effectiveness should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Scintigraphy using radionuclide luminescence imaging provides visual movement of the stomach, such as gastric emptying, that is rough and disconnected. 3 These 2 techniques represent indirect images of gastric motility. Wireless capsule endoscopy is mainly used for identifying small bowel diseases.…”
Section: Introductionmentioning
confidence: 99%